EFFECT OF LENGTHANDDEPTHOF THEDRIPTAPEON WETTING FRONT ADVANCE IN THE ROOT ZONE OF SUNFLOWR USING HYDRUS 2D/3D PROGRAM - Zahraa K. K. Al- Salihi,; Salloom B. Salim, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
A field experiment was carried out during  the spring season 2020 at the University of Baghdad to study  the effect of the length and depth of the drip tape on  wetting  advance ofsubsurface drip irrigation system using Hydrus 2D/3D program. The site was planted with sunflower  in a clay loam texture. The drip tape was installed at 0.3m below soil surfacein two lengths; 20m and 40m. The experiment was designed according to the arrangement of split plotsdesign and  with three replications. The treatments were randomly distributed and planted with sunflower crop. The results showed that the moisture contents of the 20 mlength drip tape was higher compared with  the 40 m   drip tape length. Also, the length of the tape was superior in some components of the yield if the length of the drip tape exceeded 20 m in the character of the number of seeds in one disc, and the result was a significant superiority.